THE UPTAKE, STORAGE, AND INTRACELLULAR HYDROLYSIS OF CARBOHYDRATES BY MACROPHAGES - Cohn, Zanvil A. (The Rockefeller University Press, 1969)
The exposure of cultivated mouse macrophages to sucrose (0.009–0.03 M) leads to the formation of large phase- and electron-lucent, acid phosphatase-positive vacuoles in the perinuclear region. The vacuolization process and the uptake of sucrose-(14)C is blocked by inhibitors of pinocytosis and stimulated by calf serum in the medium. These results suggest the uptake of sucrose by pinocytosis and its subsequent segregation and storage in secondary lysosomes. The addition of sucrose also increases the total content of three macrophage lysosomal hydrolases. The addition of invertase to the environment of sucrose-laden macrophages leads to the prompt shrinkage of the sucrose-containing lysosomes. This is accompanied by the intracellular hydrolysis of sucrose to fructose and glucose residues which are promptly excreted into the medium. The uptake of invertase, as indicated by the shrinkage of sucrose-containing vacuoles, is blocked by inhibitors of pinocytosis. No effect was noted when invertase was added to macrophages laden with Ficoll, a polysucrose which is not hydrolyzed by the enzyme. The influence of other carbohydrates was then investigated. Monosaccharides with molecular weights up to 220 did not produce vacuolization. However, a certain number of di-, tri-, and tetrasaccharides produced vacuolization identical with that of sucrose. Each of the disaccharides which produced vacuolization was resistant to the complement of macrophage hexosidases, whereas those that were ineffective were degraded by either macrophage or serum enzymes. The addition of β-glucosidase to cellobiose-laden macrophages resulted in the shrinkage of vacuoles but did not alter the vacuoles of sucrose containing cells. The ability of small, neutral carbohydrates to produce lysosomal swelling is dependent upon both molecular weight and their resistance to lysosomal hydrolases.